2006
DOI: 10.1152/ajpendo.00406.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular inhibition of histone deacetylation results in major enhancement of the production of IL-1β in response to LPS

Abstract: It has been postulated that the progression of human pregnancy to term is, in part, the result of a relative maternal Th 2 immunological state. This can be activated in some cell types by modifying DNA methylation and histone acetylation status. We demonstrate that the molecular inhibition of histone deacetylation, using trichostatin A (TSA), in human choriodecidual explants leads to a massive increase in lipopolysaccharide (LPS)-stimulated IL-1␤. The inhibition of histone deacetylation had no effect on LPS-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…However, more recent data indicates no difference in methylation of the APP gene in AD [9]. Furthermore, inducible nitric oxide synthase, interleukin 1, and tumor necrosis factor-α are all increased as part of the inflammatory response in AD cortex [10]; all their respective genes are methylated; and all show enhanced secretion with hypomethylation [11], [12], [13]. At the protein level, protein phosphatase 2A is methylated (probably by peptidylarginine methyltransferases or lysine methyltransferases), and its hypomethylation results in tau hyperphosphorylation [14].…”
Section: Discussionmentioning
confidence: 97%
“…However, more recent data indicates no difference in methylation of the APP gene in AD [9]. Furthermore, inducible nitric oxide synthase, interleukin 1, and tumor necrosis factor-α are all increased as part of the inflammatory response in AD cortex [10]; all their respective genes are methylated; and all show enhanced secretion with hypomethylation [11], [12], [13]. At the protein level, protein phosphatase 2A is methylated (probably by peptidylarginine methyltransferases or lysine methyltransferases), and its hypomethylation results in tau hyperphosphorylation [14].…”
Section: Discussionmentioning
confidence: 97%
“…24 TSA was also reported to suppress cell proliferation and epithelial-mesenchymal transition through inactivation of the component of LPS/TLR4 signaling pathway, such as phosphatidylinositol-3-kinase (PI3K)/Akt, p38 mitogen-activated protein kinase (MAPK), and extracellular signal-regulated kinase(ERK)1/2 pathways. 25,26 Meanwhile, Sato et al 27 reported that inhibition of HDACs with TSA in human choriodecidual explants led to a massive increase in LPS-stimulated interleukin (IL)-1β, indicating that HDACs can also negatively regulate the expression of some target genes. In our present study, by means of TLR4-siRNA- lentivirus infection, we further demonstrated that LPS stimulated the expression and activation of HDAC-4, -5, and -7 through TLR4, implying that the TLR4-mediated expression and activation of HDACs may play an important role in LPSinduced epigenetic regulation of gene expression in lung fibroblasts and phenotype transition.…”
Section: Discussionmentioning
confidence: 99%
“…DNA (CpG) methylation has been proposed to participate in this process (Mitchell 2006, Sato & Mitchell 2006, Wang et al 2008, Menon et al 2012, Mitchell et al 2012, because this epigenetic chromatin modification is involved in establishing, maintaining and altering gene expression patterns during development.…”
Section: Discussionmentioning
confidence: 99%